The impact of COVID-19 lockdown measures on symptoms control in children with asthma: A systematic review and meta-analysis of observational cohort studies - Kouis, Panayiotis; Lemonaris, Marios; Xenophontos, Eleana; Panayiotou, Andrie G.; Yiallouros, Panayiotis K. (My University, 2023)
Objectives: Reported reductions in emergency department visits and hospitalizations for asthma in previous studies have suggested a beneficial effect of the coronavirus disease of 2019 (COVID-19) lockdown measures on asthma morbidity. Nevertheless, studies relying on administrative data may overestimate the true impact of lockdowns due to changes in health-seeking behavior and reduced availability of pediatric asthma services during the pandemic. In this study, we systematically reviewed the literature and identified observational cohort studies that focused on nonadministrative data to assess the true impact of COVID-19 lockdowns on symptom control in children with asthma. Methods: A systematic literature search was conducted between January 2020 and August 2022 (International Prospective Register of Systematic Reviews ID: CRD42022354369). The impact of COVID-19 lockdowns across studies was expressed as a standardized mean difference (SMD) for continuous outcomes and as a summary relative risk (RR) for binary outcomes. Results: During the lockdown periods, the pooled asthma symptoms control test score (SMD: 1.99, 95% confidence interval [CI]: 0.75, 3.24, I2: 98.4%) and the proportion of children with well-controlled asthma (RR: 1.35, 95% CI: 1.06, 1.71, I2: 77.6%) were significantly increased. On the other hand, the pooled proportion of children with poorly controlled asthma (RR: 0.47, 95% CI: 0.38, 0.57, I2: 0.0%) was significantly decreased. Conclusions: During COVID-19 lockdowns, asthma symptoms and breakthrough disease exacerbations were significantly reduced in children with asthma. Further research is warranted on potential interventions aiming to enhance asthma control after the pandemic while taking into consideration their acceptability and potential tradeoffs.
Keywords: asthma; c-ACT; children; COVID-19; lockdown; symptoms